Ain't no silver bullet? Gun laws and suicide in the US - Joshua Ball; Günther G. Schulze; Nikita Zakharov (University of Freiburg, Department of International Economic Policy (iep), 2024)
We revisit the effect of gun laws on suicide rates in the US states in the past 30 years by departing from the correlational analysis inherent in the previous literature and, instead, leveraging an instrumental variable (IV) approach based on policy convergences between contiguous states. The empirical analysis relies on the estimated gun law stringency constructed as the number of gun laws per state-year. Our causal results show that the gun control stringency significantly reduces firearm suicide rates (both in correlational and IV estimations), corroborating previous findings; yet this decline does not translate into fewer overall suicides - contrary to what was previously found in correlational studies. This novel finding suggests that gun laws are not effective in curbing overall suicide rates.
Keywords: I12; I18; Z18; 330; Gun laws; Suicides; Endogeneity; Instrumental variables; US states